The Chinese people's liberation army - Wang, Wei; Xu, Dingxin; Zhang, Zhiyu; Yu, Cunhua; Zhang, Zhenduo; Du, Chao (China Intercontinental Press, 2012)
From the long march, through guerrilla war with the Japanese, to the victory against the Nationalist forces, the story of the PLA is the story of the founding of the People's Republic of China. Written by Chinese military experts, The Chinese People's Liberation Army provides a complete, authoritative inside story of the army of the People's Republic of China and includes sections on the organization of the PLA, the equipment currently in use and peacetime missions undertaken by the PLA